Development of stable nuclear radiation detectors based on n-silicon/cobalt-phthalocyanine heterojunctions. (March 2016) - Ray, A.; Prasad, R.; Betty, C.A.; Chandrasekhar Rao, T.V.
Abstract: n-silicon/cobalt-phthalocyanine (CoPc) heterojunction based nuclear detectors have been fabricated using thermally evaporated CoPc films. Two different thicknesses of CoPc film (viz. 100 nm and 200 nm) were tried out to make detectors by depositing on chemically polished n-Si wafers. Gold film on CoPc was used as electrical contact. The detectors were characterized by measuring their current–voltage ( I–V ) and leakage current–time ( I–t ) characteristics, followed by alpha energy spectra obtained on exposure to α-particles. Variation of alpha energy resolution with applied reverse bias voltage for each of the detectors was also studied. The detectors showed very low leakage current and high breakdown voltage as compared to conventional Au/n-Si surface barrier detectors. Finally, the durability of the detectors was established by measuring their I–V characteristics and energy resolution for nearly 15 months. Highlights: n-Si/CoPc heterojunction α-detectors of two thicknesses of CoPc (100 & 200 nm) were prepared. Detector with 100 nm CoPc, offers reliable operation of α-detectors with higher shelf life. Detectors showed very low leakage current and good α-energy resolution.